Genipin‐crosslinked decellularized annulus fibrosus hydrogels induces tissue‐specific differentiation of bone mesenchymal stem cells and intervertebral disc regeneration - Peng, Yizhong (J Tissue Eng Regen Med, 2020)
Biomaterial‐based therapy that can restore annulus fibrosus (AF) function in early stage and promote endogenous repair of AF tissues is a promising approach for AF tissue repair. In this study, we established a genipin‐crosslinked decellularized AF hydrogels (g‐DAF‐G) that are injectable and could manifest better in situ formability than noncrosslinked decellularized AF hydrogel, while preserving the capacity of directing differentiation of human bone mesenchymal stem cells (hBMSCs) towards AF cells. Hematoxylin and eosin staining, 4',6‐diamidino‐2‐phenylindole staining, and so forth showed that the majority of cellular components were removed, whereas extracellular matrix and microstructure were largely preserved. The storage modulus increased from 465.5 ± 9.4 Pa to 3.29 ± 0.24 MPa after 0.02% genipin crosslinking of decellularized AF hydrogels (DAF‐G) to form g‐DAF‐G. AF‐specific genes (COL1A1, COL5A1, TNMD, IBSP, FBLN1) were significantly higher in DAF‐G and g‐DAF‐G groups than that in control group after 21 days of culturing. g‐DAF‐G significantly restored nucleus pulposus water content and preserved intervertebral structure in vivo. Summarily, we produced a novel AF regeneration biomaterial, g‐DAF‐G, which exhibited well biocompatibility, great bioactivity, and much higher mechanical strength than DAF‐G. This study will provide an easy and fast therapeutic alternative to repair AF injuries or tears.